دور الطب الشرعي في كشف جريمة التسميم - عمرون خلود  عزوز الويزة (جامعة المسيلة, 2025)
This study aims to highlight the vital role that forensic medicine plays in uncovering poisoning crimes. It has become necessary to rely on scientific expertise to uncover the circumstances surrounding the crime and the ambiguous evidence related to it. We have divided this study into two main chapters: the first chapter deals with forensic medicine and its relationship to justice, poisons, and their types, while the second chapter focuses on uncovering the act of poisoning, including the elements that constitute the crime, forms of poisoning, and analyzing them using the analytical method. In conclusion, we found that the forensic report is an important tool for determining the criminal act and classifying it under a specific description. However, it is not considered a definitive piece of evidence in itself. It remains one of the pieces of evidence, but its evaluation ultimately depends on the personal conviction of the judge
Keywords: Keywords: forensic medicine; poisoning; poisoning crime; scientific expertise